PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PEMBUATAN ECO-ENZYME DARI LIMBAH SAYURAN UNTUK MENDUKUNG PENGELOLAAN SAMPAH RUMAH TANGGA BERKELANJUTAN - Sri Wahyuna Saragih; Wardatul Husna Irham; Ratu Mutiara Siregar; Muhammad Ikbal Aritonang; Syerlina Sari; Shaira Fitdina Amelia; Chengly Jaxon Boahlander Siahaan; Hiskia Sitanggang (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This community service initiative was designed to empower communities by providing training on converting vegetable waste into eco-enzyme as a solution for sustainable household waste management. The program adopted a participatory method involving awareness sessions, practical workshops, and ongoing assistance. Participants were introduced to material preparation, fermentation techniques, and the utilization of eco-enzyme as an eco-friendly cleaning solution and liquid fertilizer. The outcomes indicated a significant increase in participants’ understanding and practical skills in managing organic waste, along with heightened environmental awareness. Furthermore, the program fostered positive behavioral changes in reducing household organic waste and promoted the adoption of simple and affordable sustainable practices. Hence, eco-enzyme production represents a practical community-based approach to improving sustainable household waste management.